Investigating the Feasibility of Epicranial Cortical Stimulation Using Concentric-Ring Electrodes: A Novel Minimally Invasive Neuromodulation Method - Khatoun, Ahmad; Asamoah, Boateng; Mc Laughlin, Myles (Frontiers in Neuroscience, 2019)
Background Invasive cortical stimulation (ICS) is a neuromodulation method in which electrodes are implanted on the cortex to deliver chronic stimulation. ICS has been used to treat neurological disorders such as neuropathic pain, epilepsy, movement disorders and tinnitus. Noninvasive neuromodulation methods such as transcranial magnetic stimulation and transcranial electrical stimulation (TES) show great promise in treating some neurological disorders and require no surgery. However, only acute stimulation can be delivered. Epicranial current stimulation (ECS) is a novel concept for delivering chronic neuromodulation through subcutaneous electrodes implanted on the skull. The use of concentric-ring ECS electrodes may allow spatially focused stimulation and offer a less invasive alternative to ICS. Objectives Demonstrate ECS proof-of-concept using concentric-ring electrodes in rats and then use a computational model to explore the feasibility and limitations of ECS in humans. Methods ECS concentric-ring electrodes were implanted in 3 rats and pulsatile stimulation delivered to the motor cortex. An MRI based electro-anatomical human head model was used to explore different ECS concentric-ring electrode designs and these were compared with ICS and TES. Results Concentric-ring ECS electrodes can selectively stimulate the rat motor cortex. The computational model showed that the concentric-ring ECS electrode design can be optimized to achieve focused cortical stimulation. In general, focality was less than ICS but greater than noninvasive transcranial current stimulation. Conclusions ECS could be a promising minimally invasive alternative to ICS. Further work in large animal models and patients is needed to demonstrate feasibility and long-term stability.